Biomimetic versus sintered macroporous calcium phosphate scaffolds enhanced bone regeneration and human mesenchymal stromal cell engraftment in calvarial defects. (November 2021) - Brennan, Meadhbh Á.; Monahan, David S.; Brulin, Bénédicte; Gallinetti, Sara; Humbert, Paul; Tringides, Christina; Canal, Cristina; Ginebra, Maria Pau; Layrolle, Pierre
Abstract: In contrast to sintered calcium phosphates (CaPs) commonly employed as scaffolds to deliver mesenchymal stromal cells (MSCs) targeting bone repair, low temperature setting conditions of calcium deficient hydroxyapatite (CDHA) yield biomimetic topology with high specific surface area. In this study, the healing capacity of CDHA administering MSCs to bone defects is evaluated for the first time and compared with sintered beta-tricalcium phosphate (β-TCP) constructs sharing the same interconnected macroporosity. Xeno-free expanded human bone marrow MSCs attached to the surface of the hydrophobic β-TCP constructs, while infiltrating the pores of the hydrophilic CDHA. Implantation of MSCs on CaPs for 8 weeks in calvaria defects of nude mice exhibited complete healing, with bone formation aligned along the periphery of β-TCP, and conversely distributed within the pores of CDHA. Human monocyte-osteoclast differentiation was inhibited in vitro by direct culture on CDHA compared to β-TCP biomaterials and indirectly by administration of MSC-conditioned media generated on CDHA, while MSCs increased osteoclastogenesis in both CaPs in vivo . MSC engraftment was significantly higher in CDHA constructs, and also correlated positively with bone in-growth in scaffolds. These findings demonstrate that biomimetic CDHA are favorable carriers for MSC therapies and should be explored further towards clinical bone regeneration strategies. Statement of significance: Delivery of mesenchymal stromal cells (MSCs) on calcium phosphate (CaP) biomaterials enhances reconstruction of bone defects. Traditional CaPs are produced at high temperature, but calcium deficient hydroxyapatite (CDHA) prepared at room temperature yields a surface structure more similar to native bone mineral. The objective of this study was to compare the capacity of biomimetic CDHA scaffolds with sintered β-TCP scaffolds for bone repair mediated by MSCs for the first time. In vitro, greater cell infiltration occurred in CDHA scaffolds and following 8 weeks in vivo, MSC engraftment was higher in CDHA compared to β-TCP, as was bone in-growth. These findings demonstrate the impact of material features such as surface structure, and highlight that CDHA should be explored towards clinical bone regeneration strategies. Graphical abstract: Image, graphical abstract